2011
DOI: 10.1111/j.1600-0625.2011.01285.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrical impedance spectroscopy and the diagnostic accuracy for malignant melanoma

Abstract: The results suggest that electrical impedance spectra can distinguish between malignant melanoma and benign skin lesions. Although it is indicated that the accuracy of the device is clinically promising, the overall performance, and the sensitivity to thin malignant melanomas, must be improved and thoroughly validated before the instrument can be used as a routine stand-alone diagnostic decision support tool. The technique is under revision to further improve the reproducibility, specificity and sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 30 publications
1
42
3
1
Order By: Relevance
“…Recent studies have suggested that the impedance technique is capable of detecting precancerous lesions in a wide range of different tissues. Impedance technology has been shown to differentiate reliably between benign and malignant tissue in the prostate 9 and to be able to identify malignant melanoma, 10 cervical cancer, 11 and malignant tissue in the upper gastrointestinal tract. [12][13][14] In addition to several smaller pilot studies, there have been two larger studies investigating the impedance technique in malignant lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have suggested that the impedance technique is capable of detecting precancerous lesions in a wide range of different tissues. Impedance technology has been shown to differentiate reliably between benign and malignant tissue in the prostate 9 and to be able to identify malignant melanoma, 10 cervical cancer, 11 and malignant tissue in the upper gastrointestinal tract. [12][13][14] In addition to several smaller pilot studies, there have been two larger studies investigating the impedance technique in malignant lesions.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] In addition to several smaller pilot studies, there have been two larger studies investigating the impedance technique in malignant lesions. In a Europe-wide multicentre study, 10 183 patients underwent probe-based impedance spectroscopy for detection of malignant melanomas. The authors reported a sensitivity of 95% and specificity of 49% for the novel method.…”
Section: Discussionmentioning
confidence: 99%
“…Nevisense ® (SciBase AB, Stockholm, Sweden) is a diagnostic tool based on electrical impedance spectroscopy (EIS) [57]. It measures tissue resistance by administering alternating electrical currents at various frequencies to the skin.…”
Section: Introductionmentioning
confidence: 99%
“…Infrared spectroscopy [34], Raman spectroscopy [35,36], thermographic imaging [37], tissue elastography [38], fiber diffraction [39], electric impedence spectroscopy [40,41], and noninvasive genomic detection [42] may all play a role in assisting with the diagnosis of melanoma in the future. Mobile smartphone apps also offer an opportunity for patients to monitor their own skin for suspicious lesions, but current apps have, thus far, been shown to be insufficiently accurate [43,44].…”
Section: Other Technologies On the Horizonmentioning
confidence: 99%